ROLE OF SCAFFOLDING FOR REFLECTIVE THINKING ON THE MATHEMATICAL PROBLEM SOLVING - Irianto Aras; Enditiyas Pratiwi; A.Wilda Indra Nanna; Mardyanto Barumbun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Solving mathematical problems require knowledge and experiences to determine the right strategy. One of the efforts that can be used to encourage problem-solving skills is to develop reflective thinking. Reflective thinking can be a strategy to explore mathematical problem-solving abilities by questioning the answers or questioning the problems encountered so that new thoughts can be used to determine appropriate problem-solving strategies. Therefore, this study aims to explain the reflective thinking process carried out by prospective teachers in solving mathematical problems. This study used a qualitative research design with data collection through test and interview process as a triangulation stage. Participants in this study were 2 prospective teachers who carried out a reflective thinking process and were known through think aloud in implementing the test. The results showed that scaffolding was needed to complete the reflective thinking process in problem-solving. Two scaffolding positions appeared in the reflective thinking stage: (1) after the questioning and evaluating stages, scaffolding is needed as a bridge to the reasoning stage; (2) After the questioning stage, scaffolding is needed to bridge the evaluating and reasoning stages. In the reflective thinking process, scaffolding generates new knowledge to find the right problem-solving strategy.